Levodopa‐carbidopa intestinal gel in advanced Parkinson's disease: Final 12‐month, open‐label results. Issue 4 (24th December 2014) - Fernandez, Hubert H.; Standaert, David G.; Hauser, Robert A.; Lang, Anthony E.; Fung, Victor S.C.; Klostermann, Fabian; Lew, Mark F.; Odin, Per; Steiger, Malcolm; Yakupov, Eduard Z.; Chouinard, Sylvain; Suchowersky, Oksana; et al.
ABSTRACT Motor complications in Parkinson's disease (PD) are associated with long‐term oral levodopa treatment and linked to pulsatile dopaminergic stimulation. l‐dopa‐carbidopa intestinal gel (LCIG) is delivered continuously by percutaneous endoscopic gastrojejunostomy tube (PEG‐J), which reduces l‐dopa‐plasma–level fluctuations and can translate to reduced motor complications. We present final results of the largest international, prospective, 54‐week, open‐label LCIG study. PD patients with severe motor fluctuations (>3 h/day "off" time) despite optimized therapy received LCIG monotherapy. Additional PD medications were allowed >28 days post‐LCIG initiation. Safety was the primary endpoint measured through adverse events (AEs), device complications, and number of completers. Secondary endpoints included diary‐assessed off time, "on" time with/without troublesome dyskinesia, UPDRS, and health‐related quality‐of‐life (HRQoL) outcomes. Of 354 enrolled patients, 324 (91.5%) received PEG‐J and 272 (76.8%) completed the study. Most AEs were mild/moderate and transient; complication of device insertion (34.9%) was the most common. Twenty‐seven (7.6%) patients withdrew because of AEs. Serious AEs occurred in 105 (32.4%), most commonly complication of device insertion (6.5%). Mean daily off time decreased by 4.4 h/65.6% (P < 0.001). On time without troublesome dyskinesia increased by 4.8 h/62.9% (P < 0.001); on time with troublesome dyskinesia decreased by 0.4 h/22.5% (P = 0.023). Improvements persisted from week 4 through study completion. UPDRS and HRQoL outcomes were also improved throughout. In the advanced PD population, LCIG's safety profile consisted primarily of AEs associated with the device/procedure, l‐dopa/carbidopa, and advanced PD. LCIG was generally well tolerated and demonstrated clinically significant improvements in motor function, daily activities, and HRQoL sustained over 54 weeks. © 2014 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.